Scope of E-Commerce use, innovation capability, and performance: Food sector MSMEs in Indonesia - Liliana Inggrit Wijaya; Zunairoh Zunairoh; Muhammad Izharuddin; Andri Rianawati (Journal of Open Innovation: Technology, Market and Complexity)
This study aims to identify and evaluate the main factors that influence the performance of MSMEs in the food sector, focusing on two main variables: the scope of e-commerce use and the capacity for innovation. This research also uses Structural Equation Modeling (SEM) analysis techniques using smart-PLS software. The results show that technological readiness and adoption costs influence the extent to which MSMEs can utilize e-commerce, while government support plays a role in facilitating a conducive environment for the adoption of this technology. On the other hand, the factors of autonomy, proactivity, and risk-taking courage increase the innovation capacity of MSMEs, allowing them to adapt, experiment, and create unique added value in the competitive market. An in-depth understanding of the interaction between these variables is expected to provide strategic insights to improve the competitiveness and performance of food MSMEs in the digital era. The managerial implications of this study, MSMEs in the food industry in Indonesia can improve their performance through effective utilization of e-commerce, development of innovation capabilities, and government support, which can help strengthen the competitiveness of MSMEs in the increasingly competitive global market.